"Knowledge management is not dead. It has changed its appearance. And it will continue to change". (29th December 2020) - Nakash, Maayan; Bouhnik, Dan
Abstract : This study aims to examine the place and future of the Knowledge Management (KM) discipline, in view of the claims of its decline. In doing so, we explored the meanings attributed by international KM experts regarding statements made about the death of the discipline, or at the very least, its illness. A case method was chosen. The study was conducted through fifteen semi‐structured in‐depth interviews, as part of the qualitative research paradigm. The findings provide evidence not only of the vitality of the field, but also of its significant growth and impressive evolutionary development since it was founded. The Findings section presents a snapshot of KM experts' perception of the source of the pessimistic statements about the discipline and offer significant insights into the question of where this field is going. We find that the future of KM lies in developing automated mechanisms for knowledge flow that rely on machine learning tools, artificial intelligence, and advanced cognitive capabilities. Furthermore, we ponder the possibility of a rebranding of KM, given the experts' feeling that narrow, partial, or misconceived conceptions about it are prevalent. The importance of this pioneering research is reflected in the adoption of a critical‐skeptical approach, which is almost completely absent from the KM literature. The uniqueness of this research is also reflected in the voices of KM professionals. In addition to the theoretical contribution, this study has implications on the practical level regarding the necessity of the KM profession and the necessity for further empirical research in the field.